Self-guided psychological treatment for depressive symptoms: a meta-analysis. - Pim Cuijpers (Public Library of Science (PLoS), 2011)
Background A number of trials have examined the effects of self-guided psychological intervention, without any contact between the participants and a therapist or coach. The results and sizes of these trials have been mixed. This is the first quantitative meta-analysis, aimed at organizing and evaluating the literature, and estimating effect size. Method We conducted systematic literature searches in PubMed, PsycINFO and Embase up to January 2010, and identified additional studies through earlier meta-analyses, and the references of included studies. We identified seven randomized controlled trials that met our inclusion criteria, with a total of 1,362 respondents. The overall quality of the studies was high. A post-hoc power calculation showed that the studies had sufficient statistical power to detect an effect size of d = 0.19. Results The overall mean effect size indicating the difference between self-guided psychological treatment and control groups at post-test was d = 0.28 (p<0.001), which corresponds to a NNT of 6.41. At 4 to 12 months follow-up the effect size was d = 0.23. There was no indication for significant publication bias. Conclusions We found evidence that self-guided psychological treatment has a small but significant effect on participants with increased levels of depressive symptomatology.